find inverse laplace transorm : se^-2s/(s^2 + pi^2)
By property of Laplace Transform,
"\\begin{aligned}\n&\\text { if } \\mathcal{L}^{-1}(G(s))=g(t), \\text { then } \\\\\n&\\mathcal{L}^{-1}\\left(e^{-a s} G(s)\\right)=u(t-a) \\times g(t-a) \\\\\n&\\text { Now, } \\mathcal{L}(f(t))=\\frac{s e^{-2 s}}{s^{2}+\\pi^{2}}=F(s) \\\\\n&\\Rightarrow f(t)=\\mathcal{L}^{-1}(F(s))=\\mathcal{L}^{-1}\\left(\\frac{s e^{-2 s}}{s^{2}+\\pi^{2}}\\right)=\\mathcal{L}^{-1}\\left(e^{-2 s} \\times \\frac{s}{s^{2}+\\pi^{2}}\\right) \\\\\n&\\qquad \\begin{array}{l}\n\\text { But, } \\mathcal{L}^{-1}(G(s))=\\mathcal{L}^{-1}\\left(e^{-2 s} \\times G(s)\\right), \\text { where } G(s)=\\frac{s}{s^{2}+\\pi^{2}} \\\\\n\\Rightarrow f(t)=\\mathcal{L}^{-1}\\left(e^{-2 s} \\times G(s)\\right) \\\\\n\\quad=u(t-2) \\times g(t-2), \\text { from the above stated property where } \\mathrm{a}=2 \\\\\n\\quad=u(t-2) \\times \\cos (\\pi(t-2)), \\text { since } g(t)=\\cos (\\pi t)\n\\end{array} \\\\\n&\\text { Thus }, \\mathcal{L}^{-1}\\left(\\frac{s e^{-2 s}}{s^{2}+\\pi^{2}}\\right)=u(t-2) \\times \\cos (\\pi(t-2)) .\n\\end{aligned}"
Comments
Leave a comment